UJI KEPRAKTISAN MODEL EXPERIENTIAL LEARNING BERBASIS LITERA KSETRA: PENGUATAN LITERASI SAINS DI SDN BANJAR KERTEK - Kholifatul, Hania; Ahmad Khori; Desty Putri Hanifah (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Scientific literacy is an essential competency in elementary science (IPAS) learning; however, students’ scientific literacy achievement in Indonesia remains relatively low. This condition is partly caused by learning practices that tend to be theoretical and lack the use of direct experience and contextual environmental resources. This study aims to develop and describe an Experiential Learning model based on Litera Ksetra by utilizing the Litera Ksetra environment in Banjar Village as a learning context. The study employed a research and development (R&D) approach using the ADDIE model, which consists of analysis, design, development, implementation, and evaluation stages. The analysis stage was conducted to identify learning needs, student characteristics, and problems related to scientific literacy. The design stage focused on developing Experiential Learning syntax, learning materials, and scientific literacy indicators. The development stage involved constructing and validating the model based on Kolb’s Experiential Learning theory, which was modified according to the learning context. Meanwhile, the implementation and evaluation stages were conducted on a limited basis to examine the suitability of the developed model. The results of this study are in the form of a conceptual framework of the learning model, including modified Experiential Learning syntax, the roles of teachers and students, and its alignment with scientific literacy indicators, indicating that the model is systematic, easy to implement, and potentially practical in IPAS learning. The model emphasizes direct experience, reflection, and environmental interaction as the foundation for constructing contextual and meaningful scientific concepts. Therefore, this model is expected to provide both conceptual and practical contributions as a reference for teachers in designing relevant, context-based learning to enhance students’ scientific literacy.